Misoginism. Femme fatale. Androgyne - despre creatiile feminine în proza lui Mateiu Caragiale - Kornas-Warwas, Joanna (Studia Romanica Posnaniensia, 2024)
The article tells about the female characters in Mateiu Caragiale's literary work and tries to depict the characteristics of modern prose in 1930s that reflect the tendencies concentrated on the idea of „battle of the sexes". The emancipation and the changing role of women in the society led to the phenomenon of misogyny, while the image of femme fatale became a popular literary theme. On the other hand there existed the archetype of Androgyne that become a perfect incarnation of both sexes. All these aspects mentioned above found a reflection in Mateiu Caragiale's novel „Craii de Curtea Veche" proving the universal character of his work.